Aromatic and Sensory Characterization of Maturana Blanca Wines Made with Different Technologies - Ana Naranjo; Leticia Martínez-Lapuente; Belén Ayestarán; Zenaida Guadalupe; Irene Pérez; Clara Canals; Elena Adell (Beverages, 2021)
Vitis vinífera L. cv. Maturana Blanca is an autochthonous minor variety recently recovered in the Rioja Qualified Denomination of Origin (D.O.Ca Rioja, Spain) for the production of monovarietal white wines with singular and differentiated characteristics. In this paper, Maturana Blanca wines made with different technologies were analyzed by sensory analysis and aromatic profile by gas chromatography-mass detector. Maturana Blanca wines were characterized by low pH, high acidity, and yellowish tonalities. The compounds that most influenced the aroma of Maturana Blanca wines were those related to fruity (acetates and ethyl esters), floral aromas (2-phenylethanol), and spicy notes (γ-decalactone). These wines were mainly characterized by volatile compounds of fruity aromas of banana and apple. The use of pre-fermentative maceration increased the concentration of ethyl esters and acetates and produced wines with higher odor activity values, indicating a greater aromatic intensity. The aromatic profile of Maturana Blanca wines fermented in oak barrels showed a greater complexity as they were also characterized by the presence of important amounts of furfural, whiskey lactone, and eugenol. The sensory analysis confirmed the results obtained in the aromatic analysis, and described the wines as fresh and balanced in mouth, with notes of acidity and medium to high persistence. These results will contribute to a better knowledge of this white variety.